The Role of Sufism in Spreading Islam and Fighting Atonement - Ali, Isa Abdullah (DINIKA : Academic Journal of Islamic Studies, 2018)
This paper delivered the need for Islamic thought to confront the Takfiri thought, through the return of Sufi thought. Sufism does not have fatwa to kill others, Sufism talks about tolerance, the love of the Prophet, and the non-compulsion of others tojoin either Islam or the way the murid belongs to. Sufism represents the spiritual and faithful state of Islam, the core of Islam. This paper find out the role of Sufism in the spread of Islam; in the past, and the contemporary in the fight against atonement. The aim of this paper is to describe the culture of Sufism, this paper studies the intellectual of Sufism, Sufim cultural, and politics as well. This paper studied about three main axis of Sufism; the culture and history of Sufism, the role of Sufism in spreading Islam, and the role of Sufism in addressing the Takfiri thought. Based on this study, the Islamic institution and government should adopt and adapt the Sufi thought, and to address the Takfiri culture, to prevent Muslim from joining the Takfiri groups